The use of illustration in biochemistry teaching and learning - Azila Adnan, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Biochemistry is known as a complex course, especially the metabolic pathway topics. The main issue that instigate this initiative is the learners’ difficulty in understanding metabolic pathway topic(s), resulting in uninteresting learning environment. Hence, ‘the metabolic town’ illustration, that depicts three metabolic pathways (glycolysis, Krebs cycle, and electron transport chain) is used as an initiative to revive learners’ enthusiasm, which could breed interest and motivation to study this course. Trials were conducted with 35 students of Crop Science learners from the Faculty of Fisheries and Food Science, Universiti Malaysia Terengganu. Eighty-six percent (86.2%) responded ‘strongly agree’ and 13.8% responded ‘agree’ that the overall learning experience through the use of this illustration has created a positive and fun environment. Additionally, around 79% learners responded ‘strongly agree’ that their knowledge on these topics have improved while 17.2% responded ‘agree’. Nearly 100% of the learners agreed thus establish the connection between the lecture notes and the illustration. Other than that, from an intrinsic aspect, 72.4% of learners firmly agreed that this illustration aided their interest and motivation towards Biochemistry subject; while the other 27.6% agreed. 89.6% who answered strongly agreed showed that they are in favor of the use of illustration for revision while the rest agreed. Consequently, 86.2% of learners strongly agreed that the illustration boosted their understanding and boost their imagination, and the other 13.8% ‘agreed’. This study investigates how an illustration of analogy could improve the learning process.